Histomorphological Structure of The Ultimobronchial Gland In The Indigenous Geese Anser anser ( Gray lage Goose).: Fadhil Sabah Mohammed, Ahmed Mahdi Salih AL- Badri - Mohammed, Fadhil Sabah (The Iraqi Journal of Veterinary Medicine, 2010)
The indigenous geese have symmetrical pair of ultimobranchial gland, pink in color, lenticular or globular in shape. These glands are located in thoracic inlet, posterior to the parathyroid gland, dorsal to the bifurcation of brachiocephalic trunk. In young birds the left gland usually adheres to the caudal pole of parathyroid gland and usually cranio lateral to the origin of common carotid artery, while the right gland is also related to common carotid artery, but it’s separated from caudal pole of parathyroid gland. The gland is supplied by collateral branch from common carotid artery and innervated by branch from the thoracic vegal trunk and directed from the recurrent nerve. The gland is not surrounded by capsule but it’s covered by mass of adipose tissue. The parenchyma of gland consists of epithelial component supported by loose connective tissue which mostly composed of network of collagen fibers interrupted by few elastic fibers. The epithelial component of the gland consists of calcitonin producing cell or C-cell, vesicles and accessory parathyroid nodules. The C-cells are arranged in strands or cords. The connective tissue stroma of gland contains various number of follicles or vesicular structures, which are variable in shape, size, structure and secretory activity. In adult birds, the large vesicles were transformed to cystic structure, which occupied the large part of gland.